Web‐based virtual reality to enhance behavioural skills training and weight loss in a commercial online weight management programme: The Experience Success randomized trial - John Graham Thomas; Carly M. Goldstein; Dale S. Bond; Wendy Hadley; Peter W. Tuerk (Wiley, 2020)
Summary Objective Commercial online weight management programmes are popular and easily accessible but often lack training in empirically validated behaviour change strategies and produce suboptimal outcomes. This study evaluated the effects of a Web‐based virtual reality (VR) programme for enhancing behavioural skills training and weight loss when offered as an adjunct to a commercial online weight management programme. Methods N = 146 adults with overweight/obesity (body mass index [BMI] 27‐40 kg/m2) were randomized to 6 months of no‐cost access to the Weight Watchers (WW) online platform alone or enhanced with the Experience Success (WW + ES) programme, consisting of four Web‐based VR sessions for training in behavioural weight‐loss skills related to the home environment, the workplace, physical activity and social situations (i.e., a party at a friend's house). Weight was measured at the research centre at baseline, 3 and 6 months. Results Both groups achieved statistically significant weight loss across the trial, with no difference in mean ± standard error (SE) weight loss between WW and WW + ES at 3 months (2.7 ± 1.1 kg vs. 4.2 ± 1.1 kg, respectively; P = .086) but greater weight loss in WW + ES at 6 months (2.6 ± 1.3 kg vs. 4.9 ± 1.3 kg, respectively; P = .042). Conclusions This study demonstrates the potential of Web‐based VR skills training to enhance outcomes of commercial online weight management programmes that are widely accessible. Compared with traditional didactic methods for online skills training, VR simulation provides opportunities to learn behavioural skills via modelling and experiment with skills in real‐world situations. More research is needed to identify specific behavioural mechanisms by which ES may improve outcomes.